Analysis of p‐type SiOx layers as a boron diffusion source for n‐type c‐Si substrates. Issue 7 (16th March 2016) - Goyal, Prabal; Urrejola, Elias; Hong, Junegie; Voillot, Julien; i Cabarrocas, Pere Roca; Johnson, Erik
Abstract : We evaluate the use of p‐type silicon oxide (p‐SiO x ) dielectric layers as a boron diffusion source for n‐type crystalline silicon (c‐Si) substrates. The p‐SiO x layers grown on n‐type c‐Si substrates by plasma enhanced chemical vapor deposition using a gas mixture of He/hexamethyldisiloxane/CO2 /B2 H6 are thermally stable and do not peel off during annealing up to 1050 °C, making them effective diffusion sources. The layers were examined before and after annealing with characterization techniques including spectroscopic ellipsometry and secondary ion mass spectrometry. We observe that there is a reduction in the thickness of the p‐SiO x layer after annealing by about 50%, and that boron diffuses into the n‐type c‐Si substrate, forming a p + layer, limited by the formation of a carbon‐rich layer above the c‐Si surface. The concentration of holes in the diffused region was measured by the electrochemical capacitance–voltage technique, and it was found that essentially all the boron that diffused into the n‐type c‐Si was active, unaffected by the presence of carbon and oxygen atoms. The concentration of carriers can be controlled by the initial thickness of the p‐SiO x layers and the depth of the p + /n junction can be controlled by the time of annealing. A surface carrier concentration of 3 × 10 19 at cm −3 and a sheet resistance of the order of 120 Ω sq −1 was obtained upon annealing at 1050 °C for 30 min.